A meta‐analysis of the effects of bariatric surgery on fracture risk. (15th January 2018) - Zhang, Q.; Chen, Y.; Li, J.; Chen, D.; Cheng, Z.; Xu, S.; Huang, Y.; Wang, Q.
Summary: Bariatric surgery effectively treats morbid obesity. However, the negative effect of this surgery on the bone is concerning. The aim of this meta‐analysis was to investigate the fracture risk associated with bariatric surgery in morbidly obese subjects. Relevant studies published from database inception to September 2017 were identified in PubMed, Embase and the Cochrane Library. The Newcastle‐Ottawa Scale was used to evaluate the quality of the observational studies, and the Jadad score evaluated randomized controlled trials. Among the 1003 studies initially identified, five observational trials and one randomized controlled trial were eligible for inclusion. All studies included in the meta‐analysis were considered high quality. Risk for any type of fracture was higher in the surgical group than in the non‐surgical group (risk ratio [RR] 1.29, 95% confidence interval [CI] 1.18–1.42). After surgery, the fracture risk in non‐vertebral sites was significantly increased, especially in the upper limbs (RR 1.42, 95% CI 1.08–1.87; and RR 1.68, 95% CI 1.15–2.45). Compared with those with restrictive procedures, subjects who underwent mixed restrictive and malabsorptive procedures tended to have an increased fracture risk (RR 1.54, 95% CI 0.96–2.46). To conclude, bariatric surgery is associated with an increased risk of total and non‐vertebral fractures, especially in the upper limbs.